Studi eksperimental penggunaan limbah karbit sebagai adsorben untuk menurunkan emisi kendaraan bermotor - Tira, H. S.; Wirawan, M.; Padang, Y. A.; Salman, S.; Heruwasyah, H. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2020)
Motor vehicle emissions have proven lead to environmental and human health quality degradation. Therefore, efforts to reduce emissions especially motorcycles need to be done. Utilization of carbide waste has been proposed to be one of the solutions to reduce the level of emission of motorcycles. The carbide waste used is formed into granules and then installed into a reactor and placed in the exhaust line which will act as an adsorbent. The experimental study was conducted experimentally using a Yamaha Mio M3 125 CC. The results showed a reduction in exhaust emissions when using carbide waste adsorbents compared to emissions without adsorbents. The reduction was even greater when the volume of carbide waste was also greater. The reduction occurs in all types of emissions, both HC, CO, and CO2. It was obtained a reduction in emissions could reach up to 57 % for HC. However, the reduction performance cannot last long because the adsorbent has been saturated. Therefore further research is required to be performed.